2006
DOI: 10.1214/009053606000000353
|View full text |Cite
|
Sign up to set email alerts
|

Semiparametric estimation of a two-component mixture model

Abstract: Suppose that univariate data are drawn from a mixture of two distributions that are equal up to a shift parameter. Such a model is known to be nonidentifiable from a nonparametric viewpoint. However, if we assume that the unknown mixed distribution is symmetric, we obtain the identifiability of this model, which is then defined by four unknown parameters: the mixing proportion, two location parameters and the cumulative distribution function of the symmetric mixed distribution. We propose estimators for these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
182
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(190 citation statements)
references
References 34 publications
(50 reference statements)
6
182
0
Order By: Relevance
“…In a classic result, Pearson (1894) showed that the component parameters are all identified under this assumption. Similar results hold for a broad class of parametric models (Frühwirth-Schnatter, 2006) and for distributions with shape restrictions, such as symmetry (Bordes et al, 2006;Hunter et al, 2007). Note that, as we discuss in the next section, our model imposes the Normality assumption on the outcome residuals (i.e., conditional on covariates) rather than on the marginal outcome distributions.…”
Section: Principal Stratificationsupporting
confidence: 65%
“…In a classic result, Pearson (1894) showed that the component parameters are all identified under this assumption. Similar results hold for a broad class of parametric models (Frühwirth-Schnatter, 2006) and for distributions with shape restrictions, such as symmetry (Bordes et al, 2006;Hunter et al, 2007). Note that, as we discuss in the next section, our model imposes the Normality assumption on the outcome residuals (i.e., conditional on covariates) rather than on the marginal outcome distributions.…”
Section: Principal Stratificationsupporting
confidence: 65%
“…Recent developments in the semi-parametric context include (Hunter et al 2007), who obtain identifiability for univariate samples by imposing a symmetry restriction on the individual components of the mixture. Further work in the univariate case includes (Cruz-Medina and Hettmansperger 2004), who assume that the component distributions are unimodal and continuous (Ellis 2002;Bordes et al 2006).…”
Section: Identifiability Considerationsmentioning
confidence: 99%
“…Another method of constructing the estimators of these parameters is proposed in [2]. An estimator of the distribution function H 1 is constructed in [2].…”
Section: Introductionmentioning
confidence: 99%
“…The estimators proposed in the papers [2,4] are rather complicated: their evaluation is based on a numerical minimization of certain functions that depend on a sample. In the simplest case considered in [4], the function mentioned above is the U statistic.…”
Section: Introductionmentioning
confidence: 99%